Sosialisasi Dan Pelaksanaan Media Literasi Numerasi Berbasis Permainan Indoor (Program Kampus Mengajar Di Sdn Sarang Burung) - Indriani Harianja, Sri; Kurniawan, M.Willi; Angelina Titiantri, Tesya (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
The Teaching Campus Program is one of the programs planned by the Ministry of Education to improve students' abilities and numeracy literacy skills for students who are still in the school environment. The Teaching Campus Program is a form of implementing Merdeka-Learning-Campus-Merdeka (MBKM) in the form of teaching activities, technology adaptation, and Administration by providing students with assistance in the learning process in school institutions. One of them is at Sarang Burung 212 Elementary School which is located in Pematang Bedaro Simpang Limo, District Jambi Luar Kota, Regency Muaro Jambi Provinsi Jambi The scope of campus teaching focuses on students' numeracy literacy skills, by compiling and planning programs based on findings of problems at school. The program is expected to be a solution for schools in the field of understanding literacy and numeracy for students, especially through indoor games. Indoor games are games that can be implemented at various levels of education. This program is expected to have a positive impact on teachers and students on children's learning interest and motivation, especially regarding numeracy literacy. In addition to having an impact on the school, this program provides opportunities for participants in the campus teaching program such as being able to develop, improve, experience directly activities that are closely related to the nuances of the teaching and learning process.